Advances in industrial and labor relations. Vol. 15 - Lewin, David, 1943-; Kaufman, Bruce E. (Emerald, 2006)
Volume 15 of Advances in Industrial and Labor Relations (AILR) contains ten papers, four of which deal with human resource management and six of which deal with unionization. Six of the papers were originally presented in Best Papers sessions at the 57th and 58th annual meetings of the Labor and Employment Relations Association (LERA). In keeping with AILRs global perspective and global sourcing of leading research, the studies contained in these papers draw on data from the United Kingdom, France, Asia, Canada and the United States. It contains 10 papers that address human resource management and unionization.
Contains ten papers, four of which deal with human resource management and six of which deal with unionization. This work presents a global perspective with data from the UK, France, Asia, Canada, and the US.
Keywords: Industrial relations.; elektronické knihy; electronic books